Control of gene expression by FNR-like proteins in facultatively anaerobic bacteria - Mazoch, J; Kucera, I (Folia microbiologica, 2002)
Facultatively anaerobic bacteria are able to adapt to many different growth conditions. Their capability to change their metabolism optimally is often ensured by FNR-like proteins. The FNR protein of Escherichia coli functions as the main regulator during the aerobic-to-anaerobic switch. Low oxygen tensions activate this protein which is expressed constitutively and is inactive under aerobic conditions. The active form is dimeric and contains a [4Fe-4S]2+ cluster. The direct dissociation of the cluster to the [2Fe-2S]2+ cluster by the effect of oxygen leads to destabilization of the FNR dimer and to loss of its activity. The active FNR induces the expression of many anaerobic genes; the set comprises over 100 of controlled genes. Many other bacteria contain one or more FNR analogues. All these proteins form the FNR family of regulatory proteins. Properties of these proteins are very distinct, sometimes even among representatives of different strains of the same bacterial species. FNR-like proteins together with other regulators (e.g., two-component system ArcBA, nitrate-sensing system NarXL, etc.) control a complicated network of modulons that is characteristic for every species or even strain and enables fine tuning of gene expression.
Keywords: biologické modely; Bacterial Proteins; Gene Expression Regulation, Bacterial; Models, Biological; Gram-Negative Facultatively Anaerobic Rods; proteiny z Escherichia coli; proteiny obsahující železo a síru; gramnegativní fakultativně anaerobní tyčinky; bakteriální proteiny; Iron-Sulfur Proteins; Escherichia coli Proteins; regulace genové exprese u bakterií